Helicobacter pylori as a potential target for the treatment of central serous chorioretinopathy - Casella, Antonio Marcelo Barbante (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
OBJECTIVES: The objective of this study was to evaluate the relationship between the treatment of Helicobacter pylori gastric infection and changes in best-corrected visual acuity and macular detachment in patients with chronic central serous chorioretinopathy. METHODS: Seventeen patients diagnosed with central serous chorioretinopathy were examined for gastric infection with Helicobacter pylori using the urease test and gastric biopsy. Helicobacter pylori-positive patients were treated with the appropriate medication. The response to therapy was monitored by evaluating the best-corrected visual acuity and optical coherence tomography. The data were analyzed using Student's t-test before and after treatment. RESULTS: Fourteen patients (15 eyes) aged 30-56 years (mean 43.4±8.3 years) were positive for Helicobacter pylori. Most of the positive patients had gastric symptoms (78.5%); one had bilateral central serous chorioretinopathy. The mean baseline best-corrected visual acuity was 20/98 (logMAR = 0.53±0.28). Three months after starting treatment with antibiotics, the serous detachment had resolved in 14 of 15 eyes, but two cases required laser treatment. The follow-up period ranged from 6 to 27 months. The mean final best-corrected visual acuity differed significantly from baseline. CONCLUSION: Our findings suggest that Helicobacter pylori infection may be present in many chronic central serous chorioretinopathy patients and that treatment for the infection may have a favorable effect on the outcome of chronic central serous chorioretinopathy. Due to the possibility of the spontaneous regression of chronic central serous chorioretinopathy and the high prevalence of the infection in the general population, prospective and masked clinical trials are necessary to confirm that treatment for Helicobacter pylori infection may benefit patients with chronic central serous chorioretinopathy.